Association of BMI and Sport Activity Habits With Dysmenhorea - Khusnul Khotimah; RR Rhetno Arobiatul Jauzak; Siti Nurunniyah; Oktaviana Maharani; Wahyuningsih Wahyuningsih (Alma Ata University Press, 2019)
AbstractPain during menstruation or primary dysmenorrhea is the most common gynecological complaint and experienced by many women, especially in adolescence or puberty. On average more than 50% of women in each country experience primary dysmenorrhea. As many as 55% of productive age women in Indonesia experience dysmenorrhea. Although dysmenorrhea is a common complaint about adolescents, dysmenorrhea can disrupt the activities and productivity of adolescents, so that if it is not prevented or not handled properly it can result in a decrease in the quality of life and productivity of adolescents who are the next generation. Several factors that influence the incidence of dysmenorrhea are the age of the woman, age of menarche, nutritional status, stress and exercise habits. Based on these factors, Body Mass Index (BMI) and sport activity habits are factors of the healthy habits that are very useful for improving health status in general and specifically reproductive health. Knowing the relationship between Body Mass Index (BMI) and sport activity habits and the incidence of dysmenorrhea in adolescents The study was an observational study with a cross-sectional approach. All respondents numbered 142 students, experiencing menarche at a normal age. The highest frequency of menarche (mode) is at the age of 12 years as many as 50 respondents (35.2%). A respondent with a normal BMI category there are 81 respondent (57%), 44 (31%) respondent have underweight BMI category and 17 (35%) was obese. Ninety-three respondents or 69.5% have sport activity habits, 49 (34.5%) were not used to exercise. Respondents who experienced dysmenorrhea were 120 respondents (84.5%) and 22 respondents (15.5%) did not experience dysmenorrhea. BMI is not associated with dysmenorrhea incidence with P-Value = 0,07. While sport activity habits are significantly associated with dysmenorrhea in high school students with a p-value = 0.01 <α (0.05), CI = 95%, and a strong Contingency Coefficient with a value of 0.621.